The problems of development of science and education in the information society - Броннікова, Л. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The society demands to education and science in the transition to the information stage are concerning in the article. It is established that the сcommercialization of education and science, the transformation of the knowledge into commodity, the changes in disciplinary science of social life caused with social transformations of the beginning of the 21st century.